Stance and engagement in English and Arabic research article abstracts. (December 2021) - Alghazo, Sharif; Al Salem, Mohd Nour; Alrashdan, Imran
Abstract: Research in the area of intercultural rhetoric has mainly focused on academic writing in English and other languages. However, the writing of research article abstracts in English and Arabic has yet received scarce attention. To this end, this study shows how academic writers interact with their readers in both English and Arabic, or how writers express their stance and engage with readers. Eighty abstracts of research articles in the field of social sciences (40 for each language)—published in two journals (Scopus Q4): Dirasat: Human and Social Sciences and the International Journal of Interdisciplinary Educational Studies —were retrieved for quantitative and qualitative analyses using Hyland's (2005, 2019) framework. The findings are discussed in light of theories of metadiscourse and intercultural rhetoric. The analysis revealed that there are clear differences in the way academic writers express their stance and engage with readers in the two languages. Specifically, the findings showed that Arabic academic writers made less use of hedges and more use of boosters and attitude markers than English academic writers. In addition, self-mention as a stance feature was totally absent in the English abstracts but was located eight times in the Arabic ones. Finally, Arabic academic writers made less use of the engagement markers than English academic writers. The findings call for more cross-linguistic and cross-cultural analyses of academic writing in general, and research articles in particular.